Indoor air quality during cooking and cleaning: a modelling case study in a residential kitchen evaluated with real-world reference instrument measurements - Su, Yizhou; Sommariva, Roberto; Levine, James; Acton, W. Joe F.; Sahu, Ravi; Brean, James; Bloss, William J.; Mazzeo, Andrea; Nasir, Zaheer A.; Shaw, David R.; Shi, Zongbo; Hopkins, James R.; et al. (Royal Society of Chemistry (RSC), 2026)
Indoor air pollution during cooking and cleaning is influenced by complex interactions between direct emissions, ventilation-driven outdoor/indoor exchange, deposition and chemical reactions on surfaces, and indoor chemical processing. This study developed a flexible indoor single-box model (SBM-Flex) based on the INCHEM-Py indoor chemistry model to improve the representation of indoor chemistry and pollutant dynamics. The model contains chemical mechanisms of differing complexities, which can be chosen to balance computational efficiency and accuracy for specific applications. SBM-Flex was evaluated against a new observational dataset collected with reference instruments in a residential kitchen to evaluate the model's ability to simulate real-world conditions. The model qualitatively and quantitatively reproduces background conditions and episodic emission events, particularly for NOx, CO, and monoterpenes. We showed that a revised HONO formation scheme, incorporating relative humidity dependence, improves the process-level representation of indoor radical chemistry, resulting in a more realistic HONO, OH and HO2 description compared to a static HONO treatment. Simulated cooking and cleaning events highlight the importance of event-specific emissions and occupant-related effects, particularly enhanced surface deposition due to human presence, which influences O3 removal. Comparison between measurement-informed and inventory-based emissions reveals significant discrepancies, with inventory emissions often, though not uniformly, higher than real-world values. These findings underscore the need for activity-specific emission inventories and improved ventilation representation. SBM-Flex offers a promising approach for indoor air quality modelling providing valuable insights into the key processes that govern pollutant behaviour in residential environments and hence identifying priorities to reduce exposure and protect health.
Keywords: 41 Environmental Sciences; 4105 Pollution and Contamination; Health Effects of Indoor Air Pollution; 13 Climate Action